The Family Origin of the Math Gender Gap Is a White Affluent Phenomenon - Gaia Dossi; David N. Figlio; Paola Giuliano; Paola Sapienza (Institute of Labor Economics (IZA), 2020)
Previous research has shown that norms around the role of women in society could help explain the gender gap in mathematics and that these norms could be transmitted within the family. Using data from the Florida Department of Education combined with birth certificates we uncover important heterogeneity in the transmission of gender biases within the family. We find that gender role norms can explain the lower performance of girls in mathematics only in relatively affluent White families, whereas they do not apparently matter for the performance of Black girls.
Keywords: A13; I20; J16; Z1; 330; gender gap in mathematics; cultural transmission